2016
DOI: 10.1016/j.biopsycho.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Training working memory to improve attentional control in anxiety: A proof-of-principle study using behavioral and electrophysiological measures

Abstract: Trait anxiety is associated with impairments in attentional control and processing efficiency (see Berggren & Derakshan, 2013, for a review). Working memory training using the adaptive dual n-back task has shown to improve attentional control in subclinical depression with transfer effects at the behavioral and neural level on a working memory task (Owens, Koster, & Derakshan, 2013). Here, we examined the beneficial effects of working memory training on attentional control in pre-selected high trait anxious in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 60 publications
8
143
1
Order By: Relevance
“…The training related gains observed in WM capacity are in line with previous research employing the dual n-back adaptive training paradigm in both healthy and vulnerable populations (Jaeggi et al, 2008;Jaeggi et al, 2011;Owens, et al, 2013;Siegle et al, 2014;Sari et al, 2015;Course-Choi et al 2017). …”
Section: Discussionsupporting
confidence: 75%
“…The training related gains observed in WM capacity are in line with previous research employing the dual n-back adaptive training paradigm in both healthy and vulnerable populations (Jaeggi et al, 2008;Jaeggi et al, 2011;Owens, et al, 2013;Siegle et al, 2014;Sari et al, 2015;Course-Choi et al 2017). …”
Section: Discussionsupporting
confidence: 75%
“…Given the wealth of accumulating evidence documenting attentional control deficits in anxiety, the investigation that reduced WMC can explain the onset and recurrence of anxiety related symptomatology is imperative to developing clinical models of anxiety that are keen to understand the causal mechanisms behind anxiety related disorders. In this respect, there is an increasing interest in targeting working memory through adaptive cognitive training regimes meant to establish not only plasticity induced changes in cognitive function (Owens et al, 2013) but also training-dependent reductions in anxious symptomatology over time (e.g., Sari, Koster, Pourtois, & Derakshan, 2015). The current findings motivate the targeting of WMC to reduce the effects of worry related thoughts on a wide range of behavioral outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Bar-Haim, Morag, & Glickman, 2011), or to move attention towards positive stimuli (e.g., Eldar et al, 2012). Other interventions instead have been configured to enhance attentional control (e.g., Roughan & Hadwin, 2011;Hadwin & Richards, 2016; see also Owens, Koster & Derakshan, 2013;Sari, Koster, Pourtois & Derakshan, 2015 for similar work with adult populations). Researchers have demonstrated that interventions designed to directly alter attentional functioning can serve as a positive adjunct to more traditional CBT interventions for anxiety reduction in individuals who experience elevated anxious affect and who demonstrate associated attentional difficulties (Schechner et al, 2014), and may be useful for children and young people who do not show positive outcomes following conventional CBT (e.g., Bechor et al, 2014).…”
Section: Translational Implicationsmentioning
confidence: 99%